UKURAN PERUSAHAAN MEMODERASI PENGARUH KONSENTRASI KEPEMILIKAN TERHADAP NILAI PERUSAHAAN - Radhi Abdul Halim Rachmat (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2021)
This study aims to determine the moderating effect of firm size on the effect ofownership concentration as proxy for managerial ownership and institutionalownership on firm value. The sample in this study was 322 companies listed on theIndonesia Stock Exchange for the period 2014-2018. Hypothesis testing in thisresearch uses Moderated Regression Analysis (MRA) analysis technique. The resultsof this study indicate that managerial ownership has no effect on firm value whileinstitutional ownership has no effect on the firm. Firm size does not moderate theeffect of managerial ownership on firm value, while firm size does moderate theeffect of institutional ownership on firm value..